2010
DOI: 10.1021/nl101629g
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Films with Large Domain Size by a Two-Step Chemical Vapor Deposition Process

Abstract: The fundamental properties of graphene are making it an attractive material for a wide variety of applications. Various techniques have been developed to produce graphene and recently we discovered the synthesis of large area graphene by chemical vapor deposition (CVD) of methane on Cu foils. We also showed that graphene growth on Cu is a surface-mediated process and the films were polycrystalline with domains having an area of tens of square micrometers. In this paper, we report on the effect of growth parame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

50
898
7
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 919 publications
(957 citation statements)
references
References 25 publications
50
898
7
2
Order By: Relevance
“…The increased growth rate is attributed to the high catalytic activity of the Ni atoms for the decomposition of CH 4 molecules,5, 6 whereas the decreased graphene nucleation density on CuNi alloy has never been understood. According to the classical theory of crystal growth, a high carbon concentration should lead to a high growth rate and a high nucleation density simultaneously 7. The findings for the formation of graphene on the CuNi alloy substrate therefore appear completely contrary to the classical theory of crystal growth.…”
mentioning
confidence: 75%
“…The increased growth rate is attributed to the high catalytic activity of the Ni atoms for the decomposition of CH 4 molecules,5, 6 whereas the decreased graphene nucleation density on CuNi alloy has never been understood. According to the classical theory of crystal growth, a high carbon concentration should lead to a high growth rate and a high nucleation density simultaneously 7. The findings for the formation of graphene on the CuNi alloy substrate therefore appear completely contrary to the classical theory of crystal growth.…”
mentioning
confidence: 75%
“…Due to the strong scattering of charge carriers, GBs can impede electronic transport, thus degrading the electrical properties (e.g. decreasing mobility and increasing resistance) of polycrystalline graphene [78,247250]. In addition, GBs with larger grain size exhibit relatively better conductive performance [247,251].…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…decreasing mobility and increasing resistance) of polycrystalline graphene [78,247250]. In addition, GBs with larger grain size exhibit relatively better conductive performance [247,251]. On the other hand, a few experiments [209,252,253] observed that the configuration of GBs or the variation of grain sizes had little effects on the conductive properties of graphene.…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…The growth of large‐area high‐quality graphene films is fundamental for the upcoming graphene applications. Chemical vapour deposition (CVD) method offers good prospects to produce large‐size graphene films due to its simplicity, controllability and cost‐efficiency 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75. Many researches have verified that graphene can be catalytically grown on metallic substrates, like ruthenium (Ru),13, 14 iridium (Ir),15, 16 platinum (Pt),17, 18, …”
Section: Introductionmentioning
confidence: 99%
“…Achieving a uniform monolayer graphene on Ni is still a great challenge. Especially, Cu with low carbon solubility, serving as catalytic substrate, makes the continuous uniform high‐quality monolayer graphene films accessible 31, 32, 33, 34. Nowadays, the large‐scale production and transfer of graphene film from Cu foils has been realized by the roll‐to‐roll technique 69, 70.…”
Section: Introductionmentioning
confidence: 99%